O polszczyźnie w cieniu marca ’68: studium przypadku polskich Żydów – francuskich imigrantów - Magdalena Grycan (Ksiegarnia Akademicka Publishing, 2019)
Polish Language in the Shade of March ’68: the Case Study of Polish Jews – French Immigrants The paper discusses the Polish language of Jews who emigrated from Poland to France between 1967 and 1980. An analysis of excerpts from interviews which contain discourse about the attitudes of the interviewees towards their mother tongue and its transmission, will allow us to answer the following questions: What place does the Polish language occupy in everyday life of the informers? What are their feelings towards their mother tongue? And lastly, how many of them have decided to pass the Polish language to their children, and so preserve it in their families?